UNDER FIRE: news coverage of the Russian side of the war in Ukraine as combat. The case of Bruno Amaral de Carvalho - Loureiro, Luís Miguel; Pereira, Rui; Figueira, Alexandra (Brazilian journalism research, 2023)
ABSTRACT – Based on the case of freelance journalist Bruno Amaral de Carvalho, we identify and analyze the two types of battles he was involved in to guarantee coverage of the war in Ukraine for CNN Portugal, from the Russian side, between March and October 2022. As well as being involved in the information war that, since 2014, has shaped two metanarrative fields in relation to Ukraine, the journalist, the only one working on this side of the war for the Portuguese media in the period under analysis, had to combat the strategies of symbolic degradation directed at him by politicians and journalists, in the form of attacks on his character and independence. Our study collects the content produced by Bruno Amaral de Carvalho for CNN Portugal, classifying it according to these metanarrative fields, and breaks down and analyzes the process of symbolic degradation that forced the journalist into this double combat. RESUMO – Partindo do caso do jornalista freelancer Bruno Amaral de Carvalho, identificamos e analisamos os dois tipos de combates em que se envolveu para garantir a cobertura da guerra da Ucrânia, para a CNN Portugal, a partir do lado russo, entre março e outubro de 2022. Além de se envolver na guerra de informação que, desde 2014, configurou dois campos metanarrativos relativamente à Ucrânia, o jornalista, o único a trabalhar desse lado da guerra para os média portugueses no período em análise, teve de combater as estratégias de degradação simbólica que lhe foram dirigidas por políticos e jornalistas, sob a forma de ataques ao caráter e à independência. O estudo recolhe os conteúdos produzidos por Bruno Amaral de Carvalho para a CNN Portugal, classificando-os de acordo com esses campos metanarrativos, e faz a decomposição e análise ao processo de degradação simbólica que obrigou o jornalista a esse duplo combate. RESUMEN – A partir del caso del periodista freelance Bruno Amaral de Carvalho, identificamos y analizamos los dos tipos de batallas en las que estuvo involucrado para garantizar la cobertura de la guerra en Ucrania para CNN Portugal, desde el lado ruso, entre marzo y octubre de 2022. Además de estar implicado en la guerra informativa que, desde 2014, ha configurado dos campos metanarrativos en relación con Ucrania, el periodista, el único que trabajaba en este lado de la guerra para los medios portugueses en el período analizado, tuvo que combatir las estrategias de degradación simbólica dirigidas contra él por políticos y periodistas, en forma de ataques a su carácter e independencia. El estudio recoge los contenidos producidos por Bruno Amaral de Carvalho para CNN Portugal, clasificándolos según estos campos metanarrativos, y desmenuza y analiza el proceso de degradación simbólica que obligó al periodista a este doble combate.